Polska w oczach guwernera Skórzewskich, czyli zapiski księdza Pocharda z lat 1792-1833 w zbiorach Biblioteki Uniwersyteckiej w Poznaniu - Wilgosiewicz-Skutecka, Renata (Biblioteka Uniwersytecka w Poznaniu, 2011)
W zbiorach rękopisów przechowywanych w Bibliotece Uniwersyteckiej w Poznaniu znajdują się trzy tomy wspomnień Claude’a Antoine’a Pocharda – francuskiego księdza, żyjącego w czasach rewolucji francuskiej, należącego do prêtres réfractaires i w roku 1792 zmuszonego do opuszczenia ojczyzny. W latach 1792-1796 pozostawał on na emigracji w Szwajcarii, później przyjął posadę guwernera synów Józefa Skórzewskiego, starosty gnieźnieńskiego, i Heleny z Lipskich Skórzewskiej. Zapiski księdza Pocharda prowadzone w latach 1792-1833 dotyczą obu tych okresów. Ich lektura daje możliwość śledzenia losów duchownego w trudnych czasach rewolucyjnych, a także zagłębienia się w relacje naocznego świadka wydarzeń z życia rodzinnego Skórzewskich, wydarzeń ukazanych w szerszym kontekście historycznym – polskim i europejskim. Artykuł jest wprowadzeniem do badania tych rękopisów jako wielowątkowego materiału mogącego zainteresować zarówno literaturoznawców, jak i historyków, pozwalającego weryfikować wiedzę i stawiać hipotezy dotyczące dziejów jednego z najznamienitszych rodów wielkopolskich. The manuscript collection of Poznań University Library holds three volumes of the memoirs of Claude Antoine Pochard, a French Roman Catholic priest who lived during the times of the French Revolution and belonged to prêtres réfractaires and who, in 1792, was forced to leave his homeland. Between 1792 and 1796 he emigrated to Switzerland and later accepted the post of a private tutor to the sons of Józef Skórzewski, the then starosta (royal official) of Gniezno, and Helena Skórzewska née Lipska. The notes made by Father Pochard between 1792–1833 cover both mentioned periods in his life. Pochard’s notes give an interesting insight into the life history and the vicissitudes of their author in the difficult times of the revolution, as well as provide the reader with Pochard’s observations of an eyewitness of the family life of the Skórzewskis viewed in a wider historical context of the history of Poland and that of Europe. This article forms an introduction to the study on these manuscripts that are a unique combination of multi-faceted research material on different levels of analysis that is of interest not only to specialists in literature but also to historians. The material provided by the memoirs makes it possible to verify our present knowledge on the times in question and to set forth hypotheses concerning the history of the one of the most prominent families of the Wielkopolska region.
Poland in the eyes of a private tutor of the Skórzewski family, or the notes of Father Pochard from the years 1792-1833 held in Poznań University Library
Keywords: Claude Antoine Pochard; Guwerner Skórzewskich; Private tutor to the Skórzewski family; Rękopis XVIII/XIX wieku; Manuscripts of the 18th and 19th c.; Księża francuscy w czasach rewolucji francuskiej; French priests at the times of the French Revolution